Fast ion generation and its effect on ETB formation in the U-3M torsatron - Chechkin, V.V.; Grigor’eva, L.I.; Sorokovoy, E.L.; Sorokovoy, Ye.L.; Beletskii, A.A.; Slavnyj, A.S.; Burchenko, P.Ya.; Lozin, A.V.; Tsybenko, S.A.; Litvinov, A.P.; Kulaga, A.Ye.; Mironov, Yu.K.; et al. (Вопросы атомной науки и техники, 2006)
In the l=3 U-3M torsatron with RF produced and heated plasmas, a two-temperature ion energy distribution arises
with a minor group of suprathermal ions. It is shown that a possible mechanism of fast ion generation is cyclotron
heating and/or acceleration of ions by a strong RF field in the local Alfven resonance layer N||
2≈ε1 with an additional RF
field enhancement due to the coupling resonance. The observed spontaneous ETB formation is preceded by an
accumulation of high energy ions in the plasma and synchronized with their burst-like outflow to the divertor. On this
basis, it is believed that it is fast ion orbit loss that results in formation of a layer with Er shear and E×B velocity shear
accordingly at the plasma boundary, this, in turn, resulting in a damping of turbulence and turbulence-induced
anomalous transport. В 3-заходном торсатроне У-3М при ВЧ создании и нагреве плазмы образуется двухтемпературное распределение ионов по энергиям с небольшим количеством сверхтепловых ионов. Вероятным механизмом генерации быстрых ионов являются циклотронный нагрев или ускорение сильным ВЧ полем в слое локального альфвеновского резонанса при дополнительном усилении ВЧ поля вследствие резонанса связи. Спонтанное образование КТБ предваряется накоплением высокоэнергичных ионов в плазме и синхронизуется с их резким выбросом в дивертор. На этом основании считается, что образование на границе плазмы слоя с широм Еr, вызывающим подавление турбулентности и связанного с нею аномального переноса, обусловлено орбитальными потерями быстрых ионов. У 3-західному торсатроні У-3М при ВЧ створенні та нагріві плазми виникає двотемпературний розподіл іонів за енергіями з невеликою кількістю надтеплових іонів. Можливим механізмом генерації швидких іонів є циклотронний нагрів або прискорення сильним ВЧ полем у шарі локального альфвенівського резонансу при додатковому підсиленню ВЧ поля внаслідок резонансу зв’язку. Спонтанне створення КТБ випереджується накопиченням високоенергійних іонів в плазмі і синхронізується з їх різким викидом в дивертор. На цій основі вважається, що створення на границі плазми шару з широм Еr, що викликає придушення турбулентності і пов’язаного с нею аномального переносу, зумовлено орбітальними втратами швидких іонів.